Pengaruh Kejenuhan Belajar Peserta Didik dan Gaya Mengajar Guru terhadap Minat Belajar Peserta Didik - Maknunin, Binti Lu'luil; Fitrayati, Dhiah (Universitas Negeri Surabaya, 2024)
This study aims to analyze the effect of student learning saturation and teacher teaching style on students' learning interest in implementing the independent curriculum of class X in the economics subject of SMAN 22 Surabaya. The population of this study was 360 students, with a total sample of 190 students. The simple random sampling technique is the sampling technique. Using multiple linear regression analysis techniques and classical assumption tests. This research indicates that learning saturation negatively affects students' learning interests. Meanwhile, teacher learning style has a positive effect.